Melatonin protects against Nickel-induced neurotoxicity in vitro by reducing oxidative stress and maintaining mitochondrial function - Xu, Shang-Cheng; He, Min-Di; Zhong, Min; Zhang, Yan-Wen; Wang, Yuan; Yang, Lu; Yang, Ju; Yu, Zheng-Ping; Zhou, Zhou (Journal of pineal research, 2010)
:  Nickel is a potential neurotoxic pollutant. Oxidative stress is supposed to be involved in the mechanism underlying nickel‐induced neurotoxicity. Melatonin has efficient protective effects against various oxidative damages in nervous system. The purpose of this study was to investigate whether melatonin could efficiently protect against neurotoxicity induced by nickel. Here, we exposed primary cultured cortical neurons and mouse neuroblastoma cell lines (neuro2a) to different concentrations of nickel chloride (NiCl2) (0.125, 0.25, 0.5, and 1 mm) for 12 hr or 0.5 mm NiCl2 for various periods (0, 3, 6, 12, and 24 hr). We found that nickel significantly increased reactive oxygen species production and caused the loss of cell viability both in cortical neurons and neuro2a cells. In addition, nickel exposure obviously inhibited the mitochondrial function, disrupted the mitochondrial membrane potential (ΔΨm), reduced ATP production, and decreased mitochondrial DNA (mtDNA) content. However, each of these oxidative damages was efficiently attenuated by melatonin pretreatment. These protective effects of melatonin may be attributable to its roles in reducing oxidative stress and improving mitochondrial function in nickel‐treated nerve cells. Our results suggested that melatonin may have great pharmacological potential in protecting against the adverse effects of nickel in the nervous system.